Phylogeographic diversity and mosaicism of the Helicobacter pylori tfs integrative and conjugative elements - Delahay, Robin M.; Croxall, Nicola J.; Stephens, Amberley D. (BioMed Central, 2018)
Background: The genome of the gastric pathogen Helicobacter pylori is characterised by considerable variation of both gene sequence and content, much of which is contained within three large genomic islands comprising the cag pathogenicity island (cagPAI) and two mobile integrative and conjugative elements (ICEs) termed tfs3 and tfs4. All three islands are implicated as virulence factors, although whereas the cagPAI is well characterised, understanding of how the tfs elements influence H. pylori interactions with different human hosts is significantly confounded by limited definition of their distribution, diversity and structural representation in the global H. pylori population. Results: To gain a global perspective of tfs ICE population dynamics we established a bioinformatics workflow to extract and precisely define the full tfs pan-gene content contained within a global collection of 221 draft and complete H. pylori genome sequences. Complete (ca. 35-55kbp) and remnant tfs ICE clusters were reconstructed from a dataset comprising >12,000 genes, from which orthologous gene complements and distinct alleles descriptive of different tfs ICE types were defined and classified in comparative analyses. The genetic variation within defined ICE modular segments was subsequently used to provide a complete description of tfs ICE diversity and a comprehensive assessment of their phylogeographic context. Our further examination of the apparent ICE modular types identified an ancient and complex history of ICE residence, mobility and interaction within particular H. pylori phylogeographic lineages and further, provided evidence of both contemporary inter-lineage and inter-species ICE transfer and displacement. Conclusions: Our collective results establish a clear view of tfs ICE diversity and phylogeographic representation in the global H. pylori population, and provide a robust contextual framework for elucidating the functional role of the tfs ICEs particularly as it relates to the risk of gastric disease associated with different tfs ICE genotypes.